Optimal piezoelectric shape and configuration for vibration energy scavenging system - Nor Hidayati Diyana binti Nordin (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
For years, people have been working on methods to produce efficient energy scavengers. Among the established ones are solar panels, wind turbines, hydroelectric generators and many more. These macro scale energy scavenging technologies have successfully grown in meeting the world's energy demand. However, to operate low powered electronic devices; especially when being placed in a remote area, micro scale energy scavenging comes into the light. The most promising method is via vibration energy scavenging which converts mechanical energy (from vibration) to electrical energy by the effect of coupling between mechanical variables and electric or magnetic fields. As the voltage generated greatly depends on the geometry and size of the piezoelectric material, there is a need to define an optimum shape and configuration of the piezoelectric energy scavenging system (PESS). In this research, the focus is on unimorph piezoelectric energy scavenging. Mathematical modelling, based on Euler- Bernoulli beam theory is derived as well. MATLAB and COMSOL Multi physics softwares are used to study the influence of several parameters, such as mass, length and shape in generating output voltage due to base excitations for low frequency range (0-500 Hz). From simulation results, triangular beam generates 200% more voltage compared to rectangular beam. Thus, triangular comb-shaped piezoelectric energy scavenging system is chosen the best design to derive energy for a broadband vibration. Employing comb-shaped configuration increases the number of modes in a given frequency bandwidth. In this study, two natural frequencies lie in the aforementioned frequency range, as opposed to only one natural frequency for single beam structure. In addition, by having the said geometry, the generated voltage can be maximized to serve as a voltage supply for remote sensing applications.